Targeted therapy of newly diagnosed FLT3-mutated acute myeloid leukemia. A single-center ambispective cohort study - N. K. Pastukhov; S. N. Bondarenko; A. G. Smirnova; Yu. Yu. Vlasova; D. K. Zhogolev; B. I. Ayubova; O. G. Smykova; N. P. Volkov; I. S. Moiseev; A. D. Kulagin (Онкогематология, 2025)
Background. FMS‑like tyrosine kinase 3 (FLT3) gene mutations are the most frequently detected genetic aberrations in adult patients with newly diagnosed acute myeloid leukemia (AML), identified in approximately 30 % of patients. The addition of midostaurin, an FLT3 tyrosine kinase inhibitor, to standard therapy and after allogeneic hematopoietic stem cell transplantation (allo‑HSCT) improves overall (OS) and event‑free survival (EFS).   Aim. To evaluate the effect of adding midostaurin to standard therapy in adult patients with FLT3‑mutated AML. To evaluate the impact of allo‑HSCT performed in first complete remission on the survival of patients treated in combination with midostaurin.   Materials and methods. The study enrolled 276 patients with newly diagnosed AML with FLT3 mutation. 153 of them received combination therapy with midostaurin, 123 – first‑line therapy without FLT3 inhibitors. In the combination therapy group allo‑HSCT in first complete remission was performed in 35 (22.9 %) patients.   Results. The response rate was higher in the combination therapy group and was 84 % versus 66 % in the control group (p < 0.01). with a median follow‑up of 19 (2–130) months, the median OS was not achieved in both groups. The 18‑month OS was 60 % (95 % confidence interval (CI) 50–69) in the midostaurin group and 53 % (95 % CI 43–61) without it (p = 0.12). Median EFS was 11.6 months (95 % CI 9.1–13.8) and 6.7 months (95 % CI 4.2–10.2) respectively (p = 0.046). The 18‑month EFS was 33 % (95 % CI 24–42) and 31 % (95 % CI 23–40). In multivariate analysis, factors associated with worse EFS were older age and FLT3 internal tandem duplication. Age, leukocytosis at the time of diagnosis, and the presence of unfavorable cytogenetic abnormalities had a negative effect on EFS. Midostaurin therapy was associated with EFS improvement. In a landmark analysis with a 6‑month time point, OS was 89 % (95 % CI 69–96) in the allo‑HSCT group versus 38 % without it (95 % CI 20–55) (p = 0.002). EFS was 75 % (95 % CI 50–88) and 13 % (95 % CI 5–26), respectively (p <0.001).   Conclusion. The addition of midostaurin to standard treatment contributes to an increased response rate and improved survival in patients with FLT3‑mutated AML. Allo‑HSCT in first complete remission remains the preferred option for remission consolidation in patients treated with tyrosine kinase inhibitors.